The Effect of Self-Leadership Effectiveness on Academic Achievement Through Time Management of Working Students - Kumala Vera Dewi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine and analyze the effect of self-leadership on academic achievement through time management for students who also work at STIE Bina Karya. The population of this study was 198 students of the Tutorial class of the STIE Bina Karya Tebing Tinggi Management study program. The sampling method is to use the Slovin formula (α = 10%), resulting in a sample size of 67 respondents. The data collection technique is to use a questionnaire distributed to research respondents. The data processing technique used is PLS (Partial Least Square) with the help of SmartPLS software. The results showed that self-leadership has a positive and significant effect on academic achievement, self-leadership has a positive and significant effect on time management, time management has a positive and significant effect on academic achievement, time management on academic achievement, and time management can mediate the influence between self-leadership on academic achievement.